2012
DOI: 10.1097/mco.0b013e32834feab4
|View full text |Cite
|
Sign up to set email alerts
|

Role of polyunsaturated fatty acids and lipid peroxidation on colorectal cancer risk and treatments

Abstract: Recent findings CRC is one of the most overriding threats to public health. Despite a broad range of treatments, up to 50% of patients will inevitably develop incurable metastatic disease. Peroxidation of PUFAs contributes to augmentation of oxidative stress and causes in consequence inflammation, which is one of the possible carcinogenic factors of CRC. End products of PUFAs might be used as biomarkers for CRC detection and surveillance for treatment. They also have cytotoxic effect in CRC cells. Experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 58 publications
1
28
0
1
Order By: Relevance
“…Lipid peroxidation products, including primary products, peroxides (eCeOeOH) and also one of its end products, MDA, might be the main cause of PUFA-induced DNA damages, 17 which may lead to apoptosis and then cell death. Lu et al found an increase in plasma MDA concentration that might contribute to the inhibitory Table 2 Apoptosis analysis in LS174T and HT29 cells after pre-incubation of 4 h with EPA or DHA 50 mmol/L in combination with radiotherapy (4 Gy) by using fluoresenceactivated cell sorter analysis with annexin V/fluorescein isothiocyanate labeling.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation products, including primary products, peroxides (eCeOeOH) and also one of its end products, MDA, might be the main cause of PUFA-induced DNA damages, 17 which may lead to apoptosis and then cell death. Lu et al found an increase in plasma MDA concentration that might contribute to the inhibitory Table 2 Apoptosis analysis in LS174T and HT29 cells after pre-incubation of 4 h with EPA or DHA 50 mmol/L in combination with radiotherapy (4 Gy) by using fluoresenceactivated cell sorter analysis with annexin V/fluorescein isothiocyanate labeling.…”
Section: Discussionmentioning
confidence: 99%
“…This type of peroxidation is a chemical process, in which unsaturated fatty acids of lipids are damaged by free radicals and oxygen under lipoperoxides formation. Lipoperoxides are unstable and decompose to form a wide range of compounds including reactive carbonyl compounds, especially certain aldehydes (malondialdehyde (MDA), 4-hydroxy-2-nonenal (4-HNE)) [15][16][17][18][19][20][21][22] that damage cells by the binding the free amino groups of amino acids of proteins. Consequently, the proteins' aggregates become less susceptible to proteolytic degradation [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, data on association of tissue biomarker with colon or rectal cancer risk was not provided by the original studies, respectively. Given that therapeutic strategy for colon cancer and rectal cancer may differ [2], [44], future epidemiological studies should further investigate whether LC n-3 PUFA in human tissues could be beneficial for colon or rectal cancer, respectively. Fourthly, the limited numbers of cohort studies included in this meta-analysis might diminish the statistical power to detect the association between biospecimen LC n-3 PUFA and CRC risk.…”
Section: Discussionmentioning
confidence: 99%